Maduran Language Interference to Arabic Language: a Study of Community Conversational Interference in the Village of Kademangan, Bondowoso - Devi Suci Windariyah (Sekolah Tinggi Agama Islam Syaichona Moh. Cholil Bangkalan, 2021)
Abstrak:This research to describe the Madura language interference to Arabic language in pronounsation of Arabic village society in Kademangan Bondowoso.The society of Arabic village speak with Multilanguage. There are Madura, Arabic and Indonesia language. The theory basement in this research is related to sociolinguistics, Research method that is used qualitative descriptive method. Data collecting technique uses listening, record and write method. From results of this research can be concluded that there are two interference at Arabic Village In Kademangan Bondowoso. Interference Phonological caused by the changes and vocal phonemes removal, so also with morfem interference uses when makes the word with afix. The Madura languge affixes use to make the word of Arabic language.